Documentary Dilemmas : Frederick Wiseman's Titicut Follies - Anderson, Carolyn, 1939- (Book collections on Project MUSE., 1991)
A case history of the only American film under court-imposed restrictions for reasons other than obscenity or national security. Titicut Follies is an excoriating depiction of conditions in the Massachusetts Correctional Institution at Bridgewater, a prison-hospital for the criminally insane. The Commonwealth of Massachusetts took Wiseman to court, seeking to prevent the exhibition of Titicut Follies soon after its release in 1967. This account of the Titicut Follies case is based on ten years of research and relies on interviews, journalistic accounts, and especially on the legal record, including the Commonwealth v. Wiseman transcript, to describe the entire process of independent documentary filmmaking. The trials of Titicut Follies raise crucial questions about the relation of social documentary to its subjects and audiences.